Inside the Joint of Inflammatory Arthritis Patients: Handling and Processing of Synovial Tissue Biopsies for High Throughput Analysis - Floudas, Achilleas; Gorman, Aine; Neto, Nuno; Monaghan, Michael G.; Elliott, Zoe; Fearon, Ursula; Marzaioli, Viviana (Frontiers in Medicine, 2022)
Inflammatory arthritis is a chronic systemic autoimmune diseases of unknown aetiology, which affect the joint. If untreated, these diseases can have a detrimental effect on the patient’s quality of life, leading to disabilities, and therefore, exhibit a significant socioeconomic impact. While studies of immune cell populations in arthritis patient’s peripheral blood have been informative regarding potential immune cell dysfunction and possible patient stratification, there are considerable limitations in identifying the early events that lead to synovial inflammation. The joint, as the site of inflammation in inflammatory arthritis and the local microenvironment, exhibit unique characteristics that contribute to disease pathogenesis. Understanding the contribution of immune and stromal cell interactions in the inflamed joint has been met with several technical challenges. Additionally, the limited availability of synovial tissue biopsies is a key incentive for the utilisation of high-throughput techniques in order to maximise information gain. This study aims to provide an overview of key methods and novel techniques that are used in the handling, processing and analysis of synovial tissue biopsies and the potential synergy between these techniques. Herein, we describe the utilisation of high dimensionality flow cytometric analysis, single cell RNA sequencing, ex vivo functional assays and non-intrusive, metabolic characterisation of synovial cells on a single cell level based on fluorescent lifetime imaging microscopy. Additionally, we provide important points of consideration regarding the effect of different storage and handling techniques on downstream analysis of synovial tissue samples. The introduction of new powerful techniques in the study of synovial tissue inflammation, brings new challenges but importantly, significant opportunities. Implementation of novel approaches will accelerate our path towards understanding of the mechanisms involved in the pathogenesis of inflammatory arthritis and lead to the identification of new avenues of therapeutic intervention.